Interculturalisation as transforming praxis : the case of the church of Central Africa Presbyterian Blantyre synod urban ministry - Abale-Phiri, Hastings Matemba (Stellenbosch : University of Stellenbosch, 2011)
Thesis (DTh (Practical Theology and Missiology))--University of Stellenbosch, 2011.